(untitled) (Homoeopathy for All, 2024)
“Epistaxis” is the medical term for a nosebleed. A nosebleed, meaning a loss of blood from the tissue that lines the inside of your nose, can occur in one or both nostrils. Usually, it only affects one nostril. Your nose has many tiny blood vessels in it. These vessels help warm and moisten the air you breathe. But they lie close to the inner surface of your nose. When air moves through your nose, it can dry and irritate your blood vessels. This makes them very easy to injure or break, causing a nosebleed. Although bothersome, most nosebleeds aren’t serious. Anyone can get epistaxis. Most people will have at least one case in their lifetime. However, some people are more likely to have a nosebleed. They include: